2016
DOI: 10.1021/acs.biomac.6b01375
|View full text |Cite|
|
Sign up to set email alerts
|

Switching from Controlled Ring-Opening Polymerization (cROP) to Controlled Ring-Closing Depolymerization (cRCDP) by Adjusting the Reaction Parameters That Determine the Ceiling Temperature

Abstract: Full control over the ceiling temperature (Tc) enables a selective transition between the monomeric and polymeric state. This is exemplified by the conversion of the monomer 2-allyloxymethyl-2-ethyl-trimethylene carbonate (AOMEC) to poly(AOMEC) and back to AOMEC within 10 h by controlling the reaction from conditions that favor ring-opening polymerization (Tc > T0) (where T0 is the reaction temperature) to conditions that favor ring-closing depolymerization (Tc < T0). The ring-closing depolymerization (RCDP) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
86
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(88 citation statements)
references
References 64 publications
1
86
1
Order By: Relevance
“…We begin our exploration of reversible polymerization approaches in ROP systems. [48,49,[51][52][53][54][55][56] As one of the most popular controlled polymerization strategies, ROP of cyclic monomers has emerged as a useful synthetic route to prepare technologically interesting polymers with desirable architectures and specific properties. In particular, nucleophile-initiated ROP in the presence of metal-or organocatalyst allows the polymerization to proceed in a controlled manner, affording polymers with pre-determinable molecular weights and narrow molecular weight distributions.…”
Section: Reversible Polymerization In Ring-opening Polymerization Sysmentioning
confidence: 99%
See 3 more Smart Citations
“…We begin our exploration of reversible polymerization approaches in ROP systems. [48,49,[51][52][53][54][55][56] As one of the most popular controlled polymerization strategies, ROP of cyclic monomers has emerged as a useful synthetic route to prepare technologically interesting polymers with desirable architectures and specific properties. In particular, nucleophile-initiated ROP in the presence of metal-or organocatalyst allows the polymerization to proceed in a controlled manner, affording polymers with pre-determinable molecular weights and narrow molecular weight distributions.…”
Section: Reversible Polymerization In Ring-opening Polymerization Sysmentioning
confidence: 99%
“…Inspired by this pioneering work, Albertsson's team continued the study on AOMEC and first demonstrated the reversible ROP of this six-membered cyclic carbonate monomer in 2016. [49] It was concluded that the equilibrium between controlled ROP of AOMEC and controlled ring-closing depolymerization (RCDP) of poly(AOMEC) were dictated by various reaction parameters such as monomer concentration, reaction temperature, and even solvents. In their approach, AOMEC was polymerized by ROP in the presence of organocatalyst, that is, 1,8-diazabicyclo(5.4.0)undec-7-ene (DBU) in either bulk or different solvents (Figure 1a).…”
Section: Reversible Polymerization In Ring-opening Polymerization Sysmentioning
confidence: 99%
See 2 more Smart Citations
“…[9][10][11][12][13] The equilibrium behavior is clearly seen during the ring-opening polymerization of cyclic monomers, where, residual monomer will be present regardless of the reaction time and catalytic system employed. [14][15][16][17] The implications of residual monomer in the material or in the reaction mixture depend on the end-use. Obviously, for polymer synthesis the amount of residual monomer should be as low as possible; however, for monomer synthesis the opposite is advantageous.…”
Section: Introductionmentioning
confidence: 99%